2023
DOI: 10.1111/eea.13336
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent effect of methyl eugenol on male mating success of the peach fruit fly, Bactrocera zonata

Abstract: The peach fruit fly, Bactrocera zonata (Saunders) (Diptera: Tephritidae), is a pest of economic importance, endemic to South and South‐East Asia. It is highly invasive and due to its quarantine pest status, it interferes with horticultural trade. Males of many Bactrocera species are strongly attracted to methyl eugenol (ME) [1,2‐dimethoxy‐4‐(2‐propenyl) benzene], a phenylpropanoid compound naturally occurring in many plant species. Feeding on ME is also reported to enhance male mating success in several Bactro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Holding maturing males beyond 4-5 days until their maturity would add costs to the programme and may decrease the quality of males as a consequence of overcrowded conditions. 51 Rasool et al 33 demonstrated that 5-day-old B. zonata males treated with ME by feeding had a mating advantage over untreated males in mating trials conducted at the onset of sexual maturity (8 days old) and older. However, holding males for 8-9 days for ME treatment is not practicable owing to financial costs, yet treating males at 5 days of age and releasing them at 6 days of age, with males gaining the mating advantage at 8-9 days of age, seems practicable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Holding maturing males beyond 4-5 days until their maturity would add costs to the programme and may decrease the quality of males as a consequence of overcrowded conditions. 51 Rasool et al 33 demonstrated that 5-day-old B. zonata males treated with ME by feeding had a mating advantage over untreated males in mating trials conducted at the onset of sexual maturity (8 days old) and older. However, holding males for 8-9 days for ME treatment is not practicable owing to financial costs, yet treating males at 5 days of age and releasing them at 6 days of age, with males gaining the mating advantage at 8-9 days of age, seems practicable.…”
Section: Discussionmentioning
confidence: 99%
“…The males and females were separated within 24 h of emergence, well before attaining sexual maturity at 8 days of age. 33 Flies used for experiments were maintained in a separate room at 25 ± 2 °C temperature, 60 ± 5% relative humidity (RH) and 14 h:10 h, light:dark photoperiod, matching the conditions in the colony holding room.…”
Section: Study Insectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 84 species of dacine fruit flies are known responders to ME [45]. Among these, ME response varies across the Bactrocera dorsalis sibling species complex, manifested through both dose sensitivity and age of males [46][47][48]. Differences in responsiveness to ME are discrete enough that they can be used as a behavioral parameter to distinguish among species in the complex [49].…”
Section: Plos Onementioning
confidence: 99%